Intravenous Dexmedetomidine Versus Dexmedetomiddine-Dexamethasone Combination A Comparative Study on Postoperative Nausea and Vomiting after Abdominal Surgeries - Asad Shameem, Faisal Tauheed, Ghulam Mustafa, Mobasher Ahmad Saeed, Sadia Majeed, Sana Ullah Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative nausea and vomiting (PONV) is a well-known and unpleasant complication after abdominal surgeries that may negatively affect recovery and increase hospitalization. Dexmedetomidine has demonstrated opioid sparing and sympatholytic effects that can potentially decrease PONV with dexamethasone being a proven antiemetic. This paper has compared the effectiveness of intravenous dexmedetomidine versus dexmedetomidine-dexamethasone combination to prevent PONV. Methods: A comparative clinical trial was done between January 2022 and March 2023 in a tertiary-care hospital. A total of 80 adult patients that were undergoing elective abdominal surgeries were recruited and grouped into 2 equal groups: Group D control group that used dexmedetomidine only, and Group DD involving dexmedetomidine and dexamethasone 8 mg. Standardized anesthesia protocols were used. The PONV incidence, nausea scores, vomiting frequency and rescue antiemetic needs were measured after 24 hours of postoperative period. The SPSS version 26 was used to conduct statistical analysis with p<0.05 being significant. Results: Group D had significantly more cases of nausea (55% vs. 22.5, p=0.003) and vomiting (37.5% vs. 12.5, p=0.01) than Group DD. The mean nausea scores as well as vomiting frequency were significantly low in the combination group. Group DD (15% vs. 45%, p=0.004) showed a decrease in the use of rescue antiemetic. The intraoperative need of fentanyl was also much smaller in the combination group (98 + 18 µg vs. 125 + 22 µg, p<0.001). There was no difference between the similar rates of bradycardia and hypotension in both groups. Conclusion: Dexmedetomidine-dexamethasone combination is much more effective than dexmedetomidine alone in the prevention of PONV and the limit use of rescue antiemetic in the post abdomen surgical times. It also reduces the need to take opioids without escalating its adverse effects, which justifies its use in multimodal perioperative management. Keywords: Dexmedetomidine, Dexamethasone, PONV, Abdominal surgery, Antiemetic.